1981
DOI: 10.1007/978-94-009-8659-6_25
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Echometry in the Diagnosis of Congenital Glaucoma

Abstract: Thirty-three eyes of 18 normal infants and children and 22 eyes of 15 infants and children in whom congenital glaucoma had been diagnosed were measured by echometry. The anterior chamber depth, vitreous length and axial length were significantly greater in glaucomatous eyes, while the lens thickness was smaller in glaucomatous eyes. The axial length of normal eyes was found to increase with age according to the equation: axial length = 18.7 + 2.245 log (age in months.) The confidence interval of the normal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 4 publications
0
21
1
Order By: Relevance
“…Furthermore, the laser interferometer used in the study by Kiss et al had a better resolution than the IOL Master used in the present study. Although congenitally glaucomatous eyes show an increased axial eye length, 20 until now only animal studies have shown that increases in IOP cause axial eye elongation, also referred to as scleral creep. 21,22 This pressure-dependent scleral creep also increases with temperature, as shown in enucleated eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the laser interferometer used in the study by Kiss et al had a better resolution than the IOL Master used in the present study. Although congenitally glaucomatous eyes show an increased axial eye length, 20 until now only animal studies have shown that increases in IOP cause axial eye elongation, also referred to as scleral creep. 21,22 This pressure-dependent scleral creep also increases with temperature, as shown in enucleated eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Ascans from patients with glaucoma or glaucoma suspect were also excluded from the analysis because of the excessive axial elongation that occurs in infantile eyes with glaucoma. 5,24 …”
Section: Axial Length Measurementsmentioning
confidence: 99%
“…3,4 In addition, glaucoma during early childhood can cause excessive axial elongation. 5 Postoperative refractive errors are usually corrected by spectacles or contact lenses. However, if the eye grows more than expected after IOL implantation, a large myopic refractive error may develop that in extreme cases may necessitate an IOL exchange.…”
Section: Purposementioning
confidence: 99%
“…Corneal changes are often the presenting features of PCG and result in the classical clinical triad of epiphora (excessive tearing of eyes), blepharospasm (involuntary blinking of the eyelids), and photophobia (light sensitivity). Corneal diameters that are asymmetric, or a corneal diameter greater than 13 mm at any age, or greater than 11.5 mm at birth (normal 9.5 mm to 10 mm at birth and 10 mm to 12 mm at two years) warrant further evaluation for glaucoma (Allingham 2005a;Kiskis 1985;Sampaolesi 1982;Stamper 2009). Other corneal changes include corneal edema, corneal haze, Haab's striae (breaks in Descemet's membrane), and corneal opacities.…”
mentioning
confidence: 99%